171 UPSR candidates became ‘undergraduates’ for a day in UMP and learned about the cyber world - UMP, PNC (2019)
A total of 171 Year 6 pupils from seven schools in Pekan and Kuantan got to experience life as university students at Universiti Malaysia Pahang (UMP) that served as a motivational boost for them to do well in the coming examination, Ujian Penilaian Sekolah Rendah (UPSR).